2022
DOI: 10.3390/nano12030356
|View full text |Cite
|
Sign up to set email alerts
|

Phytogenic Selenium Nanoparticles Elicited the Physiological, Biochemical, and Antioxidant Defense System Amelioration of Huanglongbing-Infected ‘Kinnow’ Mandarin Plants

Abstract: Citrus greening or huanglongbing (HLB) is commonly known as yellow dragon disease and affects citrus production worldwide. Therefore, it has a significant impact on and deleterious effects in the agro-industrial sector. Significant efforts have been made to combat this disease and mitigate its destructive impact on citrus production, but still, there is no effective biocompatible treatment available to control HLB disorder. This study is considered the first biocompatible approach to evaluate the potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 84 publications
8
8
0
Order By: Relevance
“…The peaks of carbon and oxygen may be surrounding the Se-NPs. These results are in agreement with [49,50].…”
Section: Transmission and Scanning Electron Microscopysupporting
confidence: 92%
See 1 more Smart Citation
“…The peaks of carbon and oxygen may be surrounding the Se-NPs. These results are in agreement with [49,50].…”
Section: Transmission and Scanning Electron Microscopysupporting
confidence: 92%
“…The pea of carbon and oxygen may be surrounding the Se-NPs. These results are in agreeme with [49,50]. All the area peaks were similar to the Joint Committee on Powder Diffraction Standards (JCPDS) of Se-NPs with the standarddcard JCPDS, file no.…”
Section: Transmission and Scanning Electron Microscopysupporting
confidence: 87%
“…In the mapping, the “carbon” and “oxygen” relate to the PPPW extract, while the “selenium” refer to the synthesis of SeNPs ( Figure 4 D–F). These outcomes are consistent with previous studies [ 68 , 69 ].…”
Section: Resultssupporting
confidence: 94%
“…In other fruits, such as pomegranate [25], grapes [43], and orange [44], ZnO NP application also increased the sugars. The foliar application of Se NPs increased the sugars in strawberry, pomegranate, and mandarin [22,27,45] because Se increases the activity of the enzyme fructose 1,6-biphosphatase, which is related to the metabolism of carbohydrates [27]. The determination of the sugar contents in fruits is an important indicator to evaluate the quality and flavor of the fruit; sugar acts as the main substrate that provides structural material and energy for the plant's defense response, hormone-signaling molecules, and regulation of the plant immune system [25,45,46].…”
Section: Total Reducing and Nonreducing Sugars In Apple Fruitsmentioning
confidence: 99%
“…In other studies, authors reported increases in the total phenols and flavonoids in fruit trees due to Zn and B NPs, such as pomegranate [25], and, in one study, the authors reported an increase in these compounds in melon with foliar applications with Zn NPs at 50 mg L −1 [38]. Se NPs at a concentration of 75 mg L −1 increased the phenols and flavonoids by up to 54.23 and 46.99%, respectively, in mandarin fruits [45]. Other researchers reported higher proportions of flavonoids than total phenols [53].…”
Section: Contents Of Total Phenols Flavonoids and Ascorbic Acidmentioning
confidence: 99%